Misbalance in Legal Relations on Russian Marketplaces - A. A. Khoroshunov (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
The article analyses specific features of legal relations between sellers and representatives of big Russian marketplaces. Special attention is paid to the new bill N 568223-8, which includes provisions on legal regulation of marketplace work. Opinions of sellers, marketplace representatives and lawyers concerning proposals of this bill were studied. As a result the research came to the conclusion that there is a serious misbalance in relations between sellers and online-platforms. Sellers often face infringements of their rights and restrictions on the part of marketplaces, imposing of ungrounded fines and penalties, violations of offer contracts. This fact is confirmed by the growing number of suits on the part of sellers and owners of delivery points against sellers. Unfortunately, enterprises of small and medium business that use marketplaces to sell their goods are deprived of adequate legal protection. Therefore, it is necessary to elaborate and realize a uniform law, which could regulate rights and obligations of all entities of online-trade and build a system of their relations. The research used methods of analysis (logical, strategic, etc.) and synthesis, induction and deduction, statistics and legal forecasting. The obtained conclusions can be used for legislative bodies of power in developing and realizing laws, as well as for representatives of business in selling goods on marketplaces and protection of their rights and interests.